(untitled) (Fiep Bulletin - online, 2016)
The purpose of this article is to socialize a new denominated method of teaching social triathlon which we will use in the practice of a complex and financially expensive activity such as triathlon in order to improve the quality of life of a community on the outskirts of one of the most poverty-stricken states Brazil, the sugarcane municipality of Deodoro, Alagoas Marechal where organized crime and numerous other social factors affect adolescents enrolled in public schools with discipline problems and risk group offer a guided training on a new method to promote the practice with little financial resources and how recyclable materials (rubber bands, pet’s bottles) teach three modes swimming, biking and running as well as multidisciplinary have the attention of a health care team are among other objectives of social triathlon, it can be said that it is great boldness? Idealize a positive approach in triathlon in these adverse conditions and succeed is exceptional and disseminate such knowledge is revolutionizing society. The methodology dry adopted some parameters of quality of life in its execution a vision of physical embodiment or motor, affective, social, cultural and Mental .Utilizando of statistical data extracted from a logbook built during the execution of an Extension Project called TRIFAL Social -Triáthlon at the Federal Institute of Alagoas - Marechal Deodoro Campus where he attended about 100 teenagers, strengthened by a student assistance policy which provided the coming of children and adolescents against the school shift, providing food, transportation and how the team training multidisciplinary health supporting actions with the involvement of doctors, nurses, social worker, nutritionist, psychologist and Education Professionals, as students, servants and community were gradually engaging and inserted in the world of triathlon and soon began compete and stand out in the State and obtained setting up medals in the national ranking.